2021
DOI: 10.1101/2021.08.30.458230
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Disentangling the flow of signals between populations of neurons

Abstract: Technological advances have granted the ability to record from large populations of neurons across multiple brain areas. These recordings may illuminate how communication between areas contributes to brain function, yet a substantial barrier remains: How do we disentangle the concurrent, bidirectional flow of signals between two populations of neurons? We therefore propose here a novel dimensionality reduction framework: Delayed Latents Across Groups (DLAG). DLAG disentangles signals relayed in both directions… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 71 publications
(129 reference statements)
0
1
0
Order By: Relevance
“…Hultman et al 2018 examined multiregion local field potential data and identified frequencybased interactions across brain regions using a Gaussian Process Factor Analysis model. Following a similar approach, Gokcen et al 2022;2023 suggested that latent variables can be divided into across-and within-region components. This model was applied to disentangle the concurrent and bidirectional communications across brain regions with a multi-output Squared Exponential kernel.…”
Section: Introductionmentioning
confidence: 99%
“…Hultman et al 2018 examined multiregion local field potential data and identified frequencybased interactions across brain regions using a Gaussian Process Factor Analysis model. Following a similar approach, Gokcen et al 2022;2023 suggested that latent variables can be divided into across-and within-region components. This model was applied to disentangle the concurrent and bidirectional communications across brain regions with a multi-output Squared Exponential kernel.…”
Section: Introductionmentioning
confidence: 99%